AN ANALYSIS OF IMPLICATURE IN â€œICE AGE 3 MOVIEâ€ - Yasinta, Yasinta; Suhartini, Lelly; Rohmana, Rohmana (Journal of Teaching of English, 2020)
This study investigated the types and the functions of conversational implicature were used in Ice Age 3 movie. The objectives of this study have identified the types and described the functions of conversational implicature were used in "Ice Age 3 Movie''. The technique of data analysis was the researcher identified the utterances which are containing conversational implicature in ice age 3 movie based on the theory of implicature which purposed by Yule and classified the utterances based on the types of conversational implicature, namely particular implicature, scalar implicature, and generalized implicature. The researcher described the function implicature are used in ice age 3 movie based on the theory of speech act classification which is proposed by Searle. The result of this study showed that there are three types of conversational implicature found on Ice Age 3 movie based on implicature theory by Yule and the researcher also found there are four functions of conversational implicature were used in Ice Age 3 movie based on a theory of speech act by Searle.